ROLE OF HR IN DIGITAL TRANSFORMATION WITH REFERENCE TO MSMES IN PUNE (International Journal of Food and Nutritional Sciences, 2022)
This research focuses on the adoption of digital HR tools and HR strategies for the digital transformation of Micro Small and Medium Enterprises (MSMEs) in the city of Pune, India. Due to the rising use of digital technology in organizational processes, this study investigates the impact of digital HRMS, mobile HR apps, and digital training platforms on employee productivity, happiness, and operational efficiency in Pune MSMEs. I combined quantitative data from surveys with qualitative insights drawn from academic literature and industry reports while doing it with a mixed-method approach. From 2018 to 2022, the number of digital HR solutions adopted steadily increased, and the survey revealed that microenterprises were the ones having the highest compound annual investment in HR digital transformation. Among the other statistical studies were the regression and hypothesis testing of how digital HR solutions increased employee satisfaction and drastically improved HR staff productivity. The ANOVA study also revealed that the use of digital tools is more efficient depending on the firm size, with large MSMEs being most benefited by their use, whereas small MSMEs are least benefited. The conclusion of the study mentions that MSMEs face the challenges of limited resources and unskilled teams and offers suggestions to digitally enhance HR clients by way of targeted coaching, strategic investments, and change administration applications. The study not only provides advice from policymakers and business execs on how to support the development of sustainable development through HR technology but also provides valuable insight into the ongoing digital revolution taking place inside MSMEs.